The Effect of Training, Work Discipline and Incentives on the Performance of PD Employees BPR Bahteramas Konawe - Raldianingrat, Welis; Heriswanto; Fitria (Fast in Social Sciences, 2025)
This study aims to explain and analyze the effect of training, work discipline, and incentives on employee performance at PD. BPR Bahteramas Konawe. The main focus of the study is to determine the extent to which the three variables contribute to improving employee performance. Data collection was carried out by distributing questionnaires to 33 employees working at PD BPR Bahteramas Konawe. The data analysis technique in this study used multiple linear regression processed with the help of Microsoft Excel and SPSS (Statistical Package for the Social Sciences) software. This method was chosen to test the simultaneous and partial effects of training, work discipline, and incentives on employee performance variables. The results of this study indicate that (1) Training, work discipline, and incentives simultaneously have a positive and significant effect on employee performance at PD. BPR Bahteramas Konawe. (2) Training partially has a insignificant effect on employee performance at PD. BPR Bahteramas Konawe. (3) Work discipline partially have a positive and significant effect on employee performance at PD. BPR Bahteramas Konawe. (4) Incentives partially have a positive and significant effect on employee performance at PD. BPR Bahteramas Konawe.